Bias Gender dalam Kewarisan menurut Ulama Bugis - Muhammad Yusuf (Al-Ulum, 2013)
Continous dialogue between textualist and contextualist about formula of inheritance where textualist refers to universality of texts and contextualist base on particular background. Most contextualists try to consider various external of texts to find core values that is justice. Formula 2 : 1, that is, â€œman gets two pieces of inheretances and woman gets one piece inheretanceâ€ (malempaâ€™ orowanewe majjujung makkunraiye) covers right and responsibility of son to his doughter. Number 2 is maximum of sonâ€™s rigth and number 1 is minimum of daughters right. This inheritance division is implemented within the Bugis culture and yet it is elastically applied. Therefore, it implies that the core value of the texts are conisedred deeper than the texts themselves. Most Bugis scholars understand that 2 : 1 as the true meaning of texts. It is a logical consequence of influence of literatures besides common method and analytical method where mostly cannot formulate concept of inheritance comprehensively.